Theoretical Study of Methane Dissociation on Pt(111) Surface Using Density Functional Theory (DFT) Calculations - Zahraa Al-Auda; Keith L. Hohn (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
In this work, methane (CH4) dissociation on Pt(111) surface dissociation was studied based on density functional theory (DFT) calculations to evaluate the nature of adsorption and to calculate the rate constant. The most stable configurations for H and CH3 were tested on the surface of Pt(111), and the results displayed that H tends to be adsorbed at the fcc site while CH3 tends to be adsorbed at the top site. The energy of barrier and rate constant of reaction were calculated and found to be (2.28 eV) and (3.21007E−08 s−1) respectively. In addition, the adsorption energy for the reactant and products to investigate the nature of adsorption of the reactant and products on Pt(111) surface either physisorption or chemisorption. The results showed that the kind of adsorption of CH4 adsorbed on the surface of Pt(111) at top site is physisorption, while CH3 and H species adsorption on the Pt(111) surface is chemisorption. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).